Role of Volume in Intra-articular steroid injection for the Treatment of Subacromial Impingement Syndrome in Combined Military Hospital(CMH) Lahore. (Journal of Pakistan Orthopaedic Association, 2019)
Objective: To find out whether increasing the volume of intra articular steroid injection for the treatment of Subacromial Impingement Syndrome(SIS) causes more pain relief and mobility than conventional small dose injection.Methods: We conducted this randomized study in Orthopedic Department of CMH Lahore Medical College from December 2018 to February 2019. All patients of subacromial impingement syndrome(SIS) with shoulder pain fulfilling the inclusion criteria were enrolled in this randomized controlled trial. After randomly dividing the patients into two groups, group A patients were administered about 10 ml of 1% Xylocane plus 40 miligram of methylprednisolone in subacromial region wile group B patients were injected 10ml of 1% xylocaine plus 40miligram of methylprednisolone plus 20 ml of normal saline. Pre injection pain in the affected shoulder was assessed in resting state and during activity with the help of Visual Analogue Scale(VAS).Pre injection shoulder motion was documented with the help of a goniometer. Post injection shoulder pain and motion was recorded immediately after the intervention in both groups and subsequently at one month and three months follow up visits.Results: A total of 100 patients with mean age of 61 years+/- 10.32 SD were equally divided in group A and group B.Post injection pain on VAS decrease by 6 to 8 points in both groups at three months follow up. Range of motion after treatment in Group A was more markedly improved by the end of 3 months than group A, with some patients experiencing almost full range of motion. But no statistically significant difference between the outcome of the two groups was found(P value > 0.05).Conclusion: The increased volume of intra articular steroid injection for the treatment of Subacromial Impingement Syndrome(SIS) has no significant effect in reducing shoulder pain and range of motion than conventional small volume injection.